Perancangan Resort Wisata Cibulan di Kota Kuningan Jawa Barat - Putri Kencana Wati; Karya Widyawati; Ukti Lutvaidah (Universitas Indraprasta PGRI, 2023)
Kuningan is one of the cities with moderate tourism development, with this development the supporting infrastructure must be well built, one of which is a resort, a resort in Kuningan, especially in Cibulan tourism, can provide a good stimulus for tourism development, the concept of tropical architecture is considered suitable to be applied to development. resorts because they adapt to the climate in Indonesia, by using symbolic analogies to enter into the essence of resort development, in the future the construction of this resort can be used as a reference for other tourist attractions in order to redevelop their tourist attractions and make the city of Kuningan the main tourist destination for tourists both domestic or international.